2014
DOI: 10.1186/1476-4598-13-151
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a gene signature of a pre-transformation process by senescence evasion in normal human epidermal keratinocytes

Abstract: BackgroundEpidemiological data show that the incidence of carcinomas in humans is highly dependent on age. However, the initial steps of the age-related molecular oncogenic processes by which the switch towards the neoplastic state occurs remain poorly understood, mostly due to the absence of powerful models. In a previous study, we showed that normal human epidermal keratinocytes (NHEKs) spontaneously and systematically escape from senescence to give rise to pre-neoplastic emerging cells.MethodsHere, this mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
(39 reference statements)
0
11
0
1
Order By: Relevance
“…Filiation-tracing assays and videomicroscopies have proven that these cells do come from the division of fully senescent mother cells 24 . A transcriptomic analysis revealed that these cells display a gene signature of pre-transformation 31 . Moreover, they exhibit a partial epithelial-mesenchymal transition (EMT) with an increase in expression of TWIST and SLUG ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Filiation-tracing assays and videomicroscopies have proven that these cells do come from the division of fully senescent mother cells 24 . A transcriptomic analysis revealed that these cells display a gene signature of pre-transformation 31 . Moreover, they exhibit a partial epithelial-mesenchymal transition (EMT) with an increase in expression of TWIST and SLUG ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PSNE cells were shown by a transcriptomics analysis to display transformed characteristics and were evidenced to be able to generate some small skin hyperplasias and non-melanoma carcinomas in nude mice assays. 22 , 24 …”
Section: Resultsmentioning
confidence: 99%
“…Several data from our group suggest that the oxidative DNA damages encountered by senescent NHEKs could be the mutagenic motor of this postsenescence neoplastic emergence (PSNE). 22 , 24 …”
mentioning
confidence: 99%
“…4 It is commonly recognized that the raison d'être for the irreversibility of senescence is to prevent proliferation of cells with unrepaired DNA damage that are at risk of neoplastic transformation. However, we and others have shown that in the case of epithelial cells a few senescent cells always spontaneously escape from the cell cycle arrest and develop clones of mutated, transformed, and tumorigenic cells, [5][6][7][8] suggesting that the senescent cell cycle arrest is not fully irreversible in this cell type. In our latest study, we compared the DNA damage occurring at senescence in a classic model of human fibroblasts undergoing replicative senescence and in keratinocytes, in which senescence is followed by neoplastic escape.…”
Section: Commentarymentioning
confidence: 99%